AN ANALYSIS ON PROCEDURE TEXTS MADE BY THE FIRST SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA IN 2009/2010 ACADEMIC YEAR - SULISTYANI, DESI EKA (2010)
This study aims at examining and identifying the elements used in procedure texts made by the first semester students of English Department of Muhammadiyah University of Surakarta in 2009/2010 academic year. This research is descriptive qualitative research. The object of the research is procedure texts analysis made by the first semester students of English Department of Muhammadiyah University of Surakarta in 2009/2010 academic year. The data is the elements of procedure texts. The method of collecting data is documentation. The technique of data analysis is describing and identifying the percentage of the elements used in procedure text. Based on the analysis, the result of the study shows that there are many variations in presenting the elements of procedure texts: two types of variations in the social function, four types of variations in the goal, seven types of variations in the material, eight types of variations in the steps (1-n), three types of variations in focusing on generalized human agent, and four types of variations in the use of temporal conjunction. The conclusion that can be drawn from this study is that the students' texts have been completed with the elements of procedure texts, but many variations are also found there.